Hubungan Bimbingan Keluarga terhadap Hasil Belajar Matematika Siswa Kelas V SD Inpres 12/79 Cellu II - Noni sagimin; Makmur Nurdin; Rosmalah Rosmalah (STKIP Andi Matappa Pangkep, 2021)
The problem in this study is the lack of guidance for students families so that it has an impact on the results of learning mathematics students. This research is a quantitative research with a correlational design that aims to determine wether there is a relationship between family guidance and learning outcomes for V grade students of SD Inpres 12/79 Cellu II. The results showed that there was a significant relationship between family guidance and mathematics learning outcomes for V grade students of SD Inpres 12/79 Cellu II with t-count (5,567) is greater (>) the t-table value (1,697), which means H0 is rejected and H1 is accepted. Based on the analysis of the date above, it can be concluded that family guidance will have an impact on the mindset of students in learning so that it will affect the motivation and learning outcomes of students in the classroom. So, the better the family guidance, the better students learning outcomes will be. From these conlisions,, the impact resulting from this study is know that good family guidance will improve student learning outcomes.